Life Course Factors Associated with Stunting in Children Aged 2-5 Years: A Path Analysis - Dewi, Ayu Rosita; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Worldwide, in 2014, 23.8% of the children under-five years of age were stunted following the WHO definition, 7.5% were wasted but 6.1% had overweight or were obese. Developing countries host the bulk of the global stunting and child mortality rate.